Verification, validation and error estimation in CFD for compressible flows. (1st March 2010) - Peter, Jacques; Lazareff, Marc; Couaillier, Vincent
As the leader of ONERA internal project ARF PRECOTION (PREcision des COdes de simulaTION) and participant to the EU project NODESIM-CFD (NOn-DEterministic SIMulation for CFD-based design methodologies) (Hirsch, 2007), ONERA/DSNA has gained experience on verification and validation with CFD codes. The first technical section of this article is devoted to a reminder about verification and validation. The three next sections present practical estimations of various errors and uncertainties (in the technical sense of upper bounds of the absolute values of an error term) appearing in verification and validation processes. Section 3 deals with the estimation of discretisation errors. Section 4 presents several methods for the propagation of uncertain inputs. Section 5 deals with the errors due to numerical parameters and lack of convergence.